- Corporate Social Responsibility As A Source Of Competitive Advantage - Case Study on Algérie Télécom - Laghouat - Ben Salem Nour EIislam Ameur; Mohamed Rida Boumellassa; Ahmida Ferhat (جامعة عمار ثليجي الاغواط, 2022)
The aim of this study is to identify the key sources of Corporate Social Responsibility and Competitive Advantage and to analyze the relations between them. Corporate Social Responsibility is an aspect of any business, Not only does it enables businesses and organizations to connect with customers but it also creates space for corporations to engage with the world around them in a positive way. Furthermore, Competitive Advantage distinguishes a company from its competitors. It contributes to higher prices and brand loyalty, establishing such an advantage is one of the most important goals of any company. The study structure is represented by CSR as independent variable and the competitive advantage as dependent variable. Also, this research is to reach the study goal of the questionnaire that was handed to a randomized sample of 45 staff members in Algeria Telecommunications Corporation in Laghouat. The survey was analysed through Structural equation modeling (SME) to form the structure of the study. The latter was carried out by the SPSS and Smart PLS softwares for the statistical analysis to determine the link and to test the hypotheses under the available data we have.